The Effect Of Moral Equity, Locus Of Control, Environmental Uncertainty, Organizational Commitment, Reward, And Motivation On Budgetary Slack: Participatory Budgeting As A Moderating Variable - Anjelika Harniaty Sinaldi; Akhmad Riduwan; Maswar Patuh Priyadi (Lead Journal of Economy and Administration, 2023)
This study aimed to examine and analyze the effect of moral equity, locus ofcontrol, environment uncertainty, organizational commitment, reward, andmotivation onbudgetary slack: participative budgeting as a moderating variable. The population was all employees who worked at Local Government Organization in East Manggarai Sub-district. Moreover, the data collection technique used purposive sampling. In line with that, there were 115 employees as the sample. Furthermore, the instrument in the data collection technique used questionnaires. The research was quantitative. Additionally, the data analysis technique used multiple linear regression. As the result, it concluded that: (a) moral equity had a negative effect on budgetary slack; (b) locus of control had a negative effect on budgetary slack; (c) motivation had a negative effect on budgetary slack, (d) participative budgeting strengthened the effect of moral equity on budgetary slack; (e) environment uncertainty did not affect on budgetary slack: (f) organizational commitment did not affect budgetary slack; (g) reward did not affect budgetary slack; (h) participative budgeting did not moderate the effect of locus of control on budgetary slack; (i) participative budgeting did not moderate the effect of environment uncertainty om budgetary slack; (j) participative budgeting did not moderate the effect of organizational commitment on budgetary slack; (k) participative budgeting did not moderate the effect of reward on budgetary slack; and (l) participative budgeting did not moderate the effect of motivation on budgetary slack.